Guidance for the Directors of Banks - Westlake, Richard (International Finance Corporation, Washington, DC, 2014)
The need for sound governance of banks worldwide has never been stronger. After the global financial crisis of 2007-2009, spectacular bank failures, whether caused by greed, incompetence, or indifference, are still occurring. This guide is intended mainly for three groups of readers: (i) new directors with experience in banking; (ii) directors who understand governance, but have no experience in banking; and (iii) new directors who have no experience of either banking or being a director. It is mainly an introduction for the directors of non-complex banks, whose main business is to take deposits and provide loans, and is not designed for the directors of large, complex banks or investment banks operating in global capital markets and dealing with complex corporate structures. We hope, however, that even relatively experienced directors of banks, and those who work with them, may find the book a useful refresher. Main topics discussed in the Guidance are: 1) where banks fit in the corporate governance framework; 2) the unique role of banks governing risk; 3) Board structures and directors' duties; and 4) effective Board decision making. Since the late Jonathan Charkham CBE wrote the first edition of this Guidance book in 2003, the world has changed dramatically. During the crisis, many household-name banks merged or disappeared. Now there is stronger supervision of banks and greater expectations of Boards, so directors need to be knowledgeable about and engaged with their bank to provide direction and hold bank management to account.